A Central Role for Monocyte-Platelet Interactions in Heart Failure - GILMER, JOHN (My University, 2015)
Heart failure (HF) is an increasingly prevalent and costly multifactorial syndrome with high morbidity and mortality rates. The exact pathophysiological mechanisms leading to the development of HF are not completely understood. Several emerging paradigms implicate cardiometabolic risk factors, inflammation, endothelial dysfunction, myocardial fibrosis, and myocyte dys- function as key factors in the gradual progression from a healthy state to HF. Inflammation is now a recognized factor in disease progression in HF and a therapeutic target. Furthermore, the monocyte–platelet interaction has been highlighted as an important pathophysiological link between inflammation, thrombosis, endothelial activation, and myocardial malfunction. The contribution of monocytes and platelets to acute cardiovascular injury and acute HF is well established. However, their role and interaction in the pathogenesis of chronic HF are not well understood. In particular, the cross talk between monocytes and platelets in the peripheral circulation and in the vicinity of the vascular wall in the form of monocyte–platelet complexes (MPCs) may be a crucial element, which influences the pathophysiology and progression of chronic heart disease and HF. In this review, we discuss the role of monocytes and platelets as key mediators of cardiovascular inflammation in HF, the mechanisms of cell activation, and the importance of monocyte–platelet interaction and complexes in HF pathogenesis. Finally, we summarize recent information on pharmacological inhibition of inflammation and studies of antithrombotic strategies in the setting of HF that can inform oppor- tunities for future work. We discuss recent data on monocyte–platelet interactions and the potential benefits of therapy directed at MPCs, particularly in the setting of HF with preserved ejection fraction.
Keywords: Heart failure (HF); Heart failure (HF)